2013
DOI: 10.3109/17518423.2012.758184
|View full text |Cite
|
Sign up to set email alerts
|

Statistical persistence and timing characteristics of repetitive circle drawing in children with ASD

Abstract: Results support the hypothesis that children with ASD have an intact ability to consistently produce continuous movements, but increased variability in production of discontinuous movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 59 publications
0
23
1
1
Order By: Relevance
“…The axial pressure of handwriting in ASD was rarely reported in previous studies. The present finding as to the mean axial pressure was conflict with a previous exploration by which reported a significantly lower value of axial force in ASD group [16] . Whereas, our results revealed a similar performance in axial force of children with ASD when compared to TD controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The axial pressure of handwriting in ASD was rarely reported in previous studies. The present finding as to the mean axial pressure was conflict with a previous exploration by which reported a significantly lower value of axial force in ASD group [16] . Whereas, our results revealed a similar performance in axial force of children with ASD when compared to TD controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of any group differences for drumming actions could be possibly because even TD children found the drumming actions hard; in fact, the complex drumming action was the most variable across all three groups (see Figure 4). Past studies have also reported greater movement variability during rhythmic upper- and lower-limb tasks such as drumming, maraca shaking, and walking (Fleury et al, 2013; Isenhower et al, 2012; Kaur et al, 2013; Nayate et al, 2012) as well as during discrete discontinuous actions (Fleury et al, 2013). Interestingly, Fleury et al, (2013) found that children with ASD demonstrated greater movement variability during discontinuous/discrete circle drawing but not during continuous circle drawing.…”
Section: Discussionmentioning
confidence: 97%
“…These differences in findings may be due to differences in task-specific demands across the two studies. We asked children to perform whole body gross motor movements to a metronome beat, whereas Fleury and colleagues assessed a fine motor action without additional temporal demands of synchronization with an external beat (Fleury et al, 2013). In terms of movement rates, in line with our findings, slower movement rates have been reported in children and adolescents with ASD during motor tasks such as drumming and repetitive hand movements (Biscaldi et al, 2014; Isenhower et al, 2012; Jansiewicz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DFA exponents (α) were calculated for every time segment to assess long-range correlations 36 , 72 , with persistence indicated by α > 0.5 for time series deviations that continue in the same direction, and anti-persistence by α < 0.5 for deviations that continue in the opposite direction 72 . DFA has been used in analyses of motor control for ASD, with evidence of long-range correlations (persistence) during a drawing task 73 . .…”
Section: Methodsmentioning
confidence: 99%